2014
DOI: 10.1039/c4ra07675c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of commercial copper current-collector foils

Abstract: The functionality and reliability of the current collector (CC) are crucial to design and fabricate electrodes for Li-ion batteries because the CC serves as the bridge between external electronic and internal Li-ion transports. Therefore, understanding the mechanical behavior of CCs is of great importance for battery design and manufacturing. In this paper, we report the measured values of the elastic moduli of six commercial copper current-collector (CCC) foils. Measurements were performed using three techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…The loading curves are shown in Figure 3 . For copper, we found an elasticity modulus of 121 GPa, with a literature value between 117 GPa and 133 GPa [ 10 , 11 , 12 ].…”
Section: Measurement Setup and Specimen Preparationsupporting
confidence: 73%
“…The loading curves are shown in Figure 3 . For copper, we found an elasticity modulus of 121 GPa, with a literature value between 117 GPa and 133 GPa [ 10 , 11 , 12 ].…”
Section: Measurement Setup and Specimen Preparationsupporting
confidence: 73%
“…[39][40][41] A metallic current collector in LIBs in contact with the electrodes and a reactive fluorine-based non-aqueous electrolyte is considerably prone to corrosion. [45][46][47][48] The corroded current collector may cause uneven power delivery and/or to complete battery failure. Even though the corrosion phenomena in SSLBs are expected to be different from those in liquid electrolyte-based LIBs, the material requirements for BPs in SSLBs are more stringent than those for current collectors in monopolar LIBs.…”
Section: Bipolar Platesmentioning
confidence: 99%
“…In terms of electronic conductivity, chemical/electrochemical stabilities, mechanical properties, cost, and abundance, however, the choice is limited to the materials implemented in LIBs, e. g., Al, Cu, Ni, and alloys, including stainless steel and Inconel. [45][46][47][48] Al is an inexpensive, highly conductive material that is readily available in the form of a thin foil with high purity, and it is most widely utilized as a current collector for PEs. Al is usually covered with thin protective oxide films and hence exhibits high corrosion resistance at high potentials (~5.0 V vs. Li/Li + ) in various electrolyte systems.…”
Section: Bipolar Platesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the physical and chemical properties of the current collector can influence the performances of LIBs [5][6][7]. Copper foil current collectors show tensile strength over 245 MPa and elongation of 5% for thicknesses ranging from 12 to 35 µm [8]. Based on electrochemical analysis, aluminum foil is the most suitable current collector for the cathode [9].…”
Section: Introductionmentioning
confidence: 99%